Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10896-016-9872-5
|View full text |Cite
|
Sign up to set email alerts
|

Mining Electronic Health Records Data: Domestic Violence and Adverse Health Effects

Abstract: Intimate partner violence (IPV) often culminates in acute physical injury, sexual assault, and mental health issues. It is crucial to understand the healthcare habits of victims to develop interventions that can drastically improve a victim's quality of life and prevent future abuse. The objective of this study is to mine de-identified and aggregated Electronic Health Record data to identify women's health issues that are potentially associated with IPV. In this study we compared health issues of female domest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 21 publications
(34 reference statements)
4
45
0
1
Order By: Relevance
“…A complete and detailed description of the data acquisition performed for this study can be found in a previously published manuscript. 15 Here, we provide a brief summary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete and detailed description of the data acquisition performed for this study can be found in a previously published manuscript. 15 Here, we provide a brief summary.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, 15 we accessed and analyzed national EHR data through the Explorys platform (Explorys Inc., an IBM company), specifically utilizing the “Explorys Enterprise Performance Management (EPM): Explore” web application to identify diseases which seem to be more prevalent among victims of IPV than the general US population. Explorys is comprised of EHR, EMR, insurance claims, and billing data sources.…”
Section: Introductionmentioning
confidence: 99%
“…Examining the prevalence of TBI among a group of domestic violence victims, researchers found that 88% of the women studied experienced more than one injury, and 81% of them had experienced loss of consciousness due to their injuries [54]. Mounting research indicates that mental health challenges domestic violence victims face may be even more disheartening [57][58][59]. Results from a meta-analysis of 207 studies show that depression, anxiety, posttraumatic stress disorder, antisocial personality disorder, and borderline personality disorder are common among domestic violence victims [57].…”
Section: Study Protocol Registration: Prospero Crd42020194003mentioning
confidence: 99%
“…Data from the CDC's National Intimate Partner and Sexual Violence Survey also suggest that IPV is associated with a myriad of negative consequences among survivors, with 27% of women and 11% of men reporting a negative impact (Smith et al., ). Victims of partner violence can experience a range of adverse health outcomes, including physical and mental health problems (Black, ; Breiding, Black, & Ryan, ; Coker, Smith, Bethea, King, & McKeown, ; Karakurt, Patel, Whiting, & Koyutürk, ; Kastello et al., ; Ulloa & Hammett, ), poor maternal health and pregnancy outcomes (Karakurt et al., ; Leone et al., ), and increased likelihood of engaging in risky behaviors (Breiding et al., ; CDC, ). Survivors also report that experiencing IPV negatively affects their ability to attend work/school, receive required medical care and legal assistance, and obtain housing services (Smith et al., ).…”
Section: Introductionmentioning
confidence: 99%